TRENDS IN YOUTH EMPLOYMENT: ROMANIA CASE OF STUDY - PATACHE, Laura (Ecoforum Journal, 2015)
Reducing poverty and creating employment are the twin challenges of Europe 2020 strategy. During the crisis period, relative poverty has been increased among 0-17 years of age group and in some Romanian development regions. The European Union is concerned in taking action on increasing youth employment, because: the youth unemployment rate is more than twice as high as the adult one; the chances for a young unemployed person of finding a job are low, when young people do work, their jobs tend to be less stable; early leavers from education and training are a high-risk group; resignation is an increasing concern; a significant percent of young people were neither in employment nor in education or training (NEETs); there are significant skills mismatches on Europe’s labour market. This paper presents the dynamics of the Romanian youth employment in the development regions of Romania between 2008 and 2014.